Kinetic study on pyrolysis of waste phenolic fibre-reinforced plastic. (25th May 2018) - Chen, Ruiyu; Xu, Xiaokang; Zhang, Yang; Lo, Siuming; Lu, Shouxiang
Highlights: Pyrolysis tests of waste phenolic FRP are conducted in a wide heating rate range. A two-step consecutive reaction model describing the pyrolysis process is proposed. Genetic algorithm is used to optimize all the kinetic parameters simultaneously. The predicted results fit well with the experimental thermogravimetric curves. The applicability of optimized parameters is validated for wider heating rates. Abstract: Pyrolysis is considered to be a promising method to recycle waste plastics for fuel or chemical feedstock. In order to provide guidance for reactor design and pyrolysis process management for recycling waste phenolic fibre-reinforced plastic (FRP), the pyrolysis behaviors of waste phenolic FRP is studied employing thermogravimetric analysis (TGA) over a wide heating rate range from 10 K/min to 70 K/min in nitrogen. A two-step consecutive reaction model is proposed to characterize the pyrolysis process. A global optimization algorithm called genetic algorithm (GA) coupled with the two-step consecutive reaction model is used to obtain all the kinetic parameters simultaneously based upon the experimental thermogravimetric data at heating rates of 10, 20 and 30 K/min. The predicted MLR and conversion curves using the optimized kinetic parameters and the two-step consecutive reaction model fit well with the experimental results not only at heating rates of 10, 20 and 30 K/min, but also at heating rates of 50, 60 and 70 K/min which are not used to obtain the kinetic parameters. The optimized kinetic parameters and the two-step consecutive reaction model may be applicable to the pyrolysis of waste phenolic FRP under more practical and complex thermal conditions that can be characterized by various heating rates.